(untitled) (Revista Sistemas de Producción Agroecológicos, 2023)
ABSTRACT The physicochemical parameters of the milk, allow us to recognize the quality of the product to be consumed through certain ranges that have been established at an international level by the United Nations Organization for Food and Agriculture and the World Health Organization, as well as by the entities in each country responsible for taking care of the population in the face of risks during access to products and services; in Colombia it corresponds to the Ministry of Social Protection, which establishes in article 6 of resolution 00001057 of March 23, 2010 the physicochemical requirements of bee seedlings, considered for the ongoing investigation. The bees of the Meliponini tribe, known as native bees without aguijón, have been little studied in relation to the characteristics of their families, limiting them to recognizing the quality of the product and being until now commercialized informally or on a small scale, without ever being recognized added value or quality certification of the production system. The study allowed us to identify aspects inherent to the physicochemical characteristics of the bee seedlings in different production systems. The identification of native bee productions was carried out through an informant and the production chain has not yet been established; In the productions, samples were obtained that were analyzed in the chemistry laboratory of the Universidad de la Amazonia, using protocols established to determine physicochemical characteristics. Fine and coarse impurities such as wings, legs, pollen, plant residues and others will be identified and soluble solids and moisture will be obtained with values between 49% and 77%, PH of 3.6 on average and free acidity of 251 meq/kg. The differences in values are associated with the location of production, vegetation and production time, as well as the production unit, but more studies on sanitary, zootechnical and property aspects are needed in the Colombian Amazon region, which contribute to activities related to native bees without aguijón.